2018
DOI: 10.2967/jnumed.117.205286
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Computational Model and Dosimetry Calculations for PET/CT of a Patient Pregnant with Twins

Abstract: The radiation dose delivered to pregnant patients during radiologic imaging procedures raises health concerns because the developing embryo and fetus are considered to be highly radiosensitive. To appropriately weigh the diagnostic benefits against the radiation risks, the radiologist needs reasonably accurate and detailed estimates of the fetal dose. Expanding our previously developed series of computational phantoms for pregnant women, we here describe a personalized model for twin pregnancy, based on an act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Other limitations of this work include the few organs considered and the use of only one CT scanner model. The construction of patient‐specific models for accurate dosimetry calculations remains a challenging issue requiring further research and development efforts . Deep learning approaches have brought revolutionary advances in the field of medical image analysis that could be useful for constructing patient‐specific models through automatic segmentation of medical images (body contours and internal organs).…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations of this work include the few organs considered and the use of only one CT scanner model. The construction of patient‐specific models for accurate dosimetry calculations remains a challenging issue requiring further research and development efforts . Deep learning approaches have brought revolutionary advances in the field of medical image analysis that could be useful for constructing patient‐specific models through automatic segmentation of medical images (body contours and internal organs).…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Council on Radiation Protection and Measurements Report no 184, 9 in addition to background radiation, the major source of ionizing radiation exposure of the American public is related to the medical exposure. Pregnant females might be exposed to different sources of ionizing radiation, including diagnostic radiology, 1,10–12 radiation therapy, 13,14 and nuclear medicine 3,15–17 procedures. The health effects of ionizing radiation on the embryo/fetus depend on their gestational age: (i) The stage of 3–4 weeks of pregnancy is supposed to be the most likely period to suffer embryo death; (ii) whereas the pregnancy at 8–15 weeks is considered to be the most sensitive for radiation risks of growth retardation, microcephaly, and severe mental disability 18–20 ; (iii) finally, at 16–40‐week gestation, fetal radiation exposure higher than 1.5 Gy can result in both growth and mental retardation 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The models were used for radiation dose assessment of fetuses and pregnant patients using positron-emitting radiotracers [23]. In addition, a patient-specific computational phantom was developed for dosimetry calculations using a PET/CT scan of a patient pregnant with twins [24]. Another study by Xie et al [25] demonstrated that patient-specific computational models can be created using an automated deep learning-based segmentation algorithm for retrospective radiation dose evaluation during high-dose procedures in a clinical setting and in research studies involving retrospective data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The average pregnant computational phantom [15][16][17][18][19][20][21][22][23][24][25][26] was adopted and recommended by the ICRP as a standard pregnant patient. To date, only a limited number of realistic fetal phantoms have been created for each pregnancy stage to demonstrate the stages of fetal development and intrauterine positioning.…”
Section: Introductionmentioning
confidence: 99%